O professor iniciante da escola do campo e sua formação : por entre espelhos... - Pereira, Oldair José Tavares (2017)
The present research is focused on the training of teachers for the Field Education, specifically the beginner teacher being inserted in the Postgraduate Program in Education (PPGEdu) of the Federal University of Mato Grosso, Campus Universitário de Rondonópolis (UFMT / CUR), Research group Investigation. It originates from the obeducation project 49/2013 of OBEDUC and develops training with beginner teachers, with up to five years of teaching. It aims to investigate how the beginning teachers of the field manifest themselves, perceive and attribute meanings to the continuous formation directed to their formative needs in the beginning of the teaching. The research subjects are six teachers, who work at the Wellington Flaviano Coelho Field School that is located in the MST settlement, Márcio Pereira in the city of São José do Povo-MT. The research deals with the insertion of the beginning teacher in the School of the Field, considering the difficulties that the beginning of career offers and the singularities of the Education of the Field. Adopting a qualitative approach the (auto) biographical method is used and the data collection took place with interviews and training memorials. The questions that guide the research are: What do the beginning teachers of the education of the field about the continued formation offered by the OBEDUC in the attendance to their formative needs so that they can minimize the impacts of this professional at the beginning of career? What do they report on the continuing education processes offered by the public education system in the last five years? How do they refer to the continued formation shared in the PPGEdu / UFMT / OBEDUC project in the last? The research revealed that teachers are aware that they need training so that they can reduce the impacts caused at the beginning of their careers, and that this, when it happens through public policy of the education system, has not met the expectations of teachers. They also reveal that continuing education that participates in the OBEDUC / UFMT project, even though it is not specific to rural education, has helped them understand the dilemmas of / in teaching practice.